Gastric Supply Manipulation to Modulate Ghrelin Production and Enhance Vascularization to the Cardia: Proof of the Concept in a Porcine Model. (February 2015) - Diana, Michele; Halvax, Peter; Pop, Raoul; Schlagowski, Isabel; Bour, Gaetan; Liu, Yu-Yin; Legner, Andras; Diemunsch, Pierre; Geny, Bernard; Dallemagne, Bernard; Beaujeux, Rémy; Demartines, Nicolas; et al.
Introduction. Selective embolization of the left-gastric artery (LGA) reduces levels of ghrelin and achieves significant short-term weight loss. However, embolization of the LGA would prevent the performance of bariatric procedures because the high-risk leakage area (gastroesophageal junction [GEJ]) would be devascularized. Aim. To assess an alternative vascular approach to the modulation of ghrelin levels and generate a blood flow manipulation, consequently increasing the vascular supply to the GEJ. Materials and methods . A total of 6 pigs underwent a laparoscopic clipping of the left gastroepiploic artery. Preoperative and postoperative CT angiographies were performed. Ghrelin levels were assessed perioperatively and then once per week for 3 weeks. Reactive oxygen species (ROS; expressed as ROS/mg of dry weight [DW]), mitochondria respiratory rate, and capillary lactates were assessed before and 1 hour after clipping (T0 and T1) and after 3 weeks of survival (T2), on seromuscular biopsies. A celiac trunk angiography was performed at 3 weeks. Results. Mean (±standard deviation) ghrelin levels were significantly reduced 1 hour after clipping (1902 ± 307.8 pg/mL vs 1084 ± 680.0; P = .04) and at 3 weeks (954.5 ± 473.2 pg/mL; P = .01). Mean ROS levels were statistically significantly decreased at the cardia at T2 when compared with T0 (0.018 ± 0.006 mg/DW vs 0.02957 ± 0.0096 mg/DW; P = .01) and T1 (0.0376 ± 0.008mg/DW; P = .007). Capillary lactates were significantly decreased after 3 weeks, and the mitochondria respiratory rate remained constant over time at the cardia and pylorus, showing significant regional differences. Conclusions. Manipulation of the gastric flow targeting the gastroepiploic arcade induces ghrelin reduction. An endovascular approach is currently under evaluation.